PRIVATE DEFENCE IN CONTEXT OF THE BATTERED WIFE WHO KILLS HER ABUSIVE HUSBAND/PARTNER Ann Elizabeth Steyn v The State (reported as S v Steyn 2010 1 SACR 411 (SCA)) - Pieter Carstens (Obiter, 2021)
In South Africa where there is a high incidence of domestic violence, it is not surprising to find our reported criminal case law abound with many examples where battered spouses have killed their abusive partners. It is to be noted that all these accused were charged with, and more often than not, convicted of murder. In all these cases extreme provocation and emotional distress ultimately led to the homicide and caused the accused to invoke either non-pathological automatism (sane automatism) and/or nonpathological criminal incapacity as defences. Consequently, it was argued on behalf of the accused that they either acted involuntarily or without criminal capacity, or at the most with diminished criminal capacity at the time of the homicide due to provocation or emotional distress. In some instances, where a voluntary act and criminal capacity were proved, the provocation/emotional distress even had the effect that the state could not prove intention beyond reasonable doubt for a conviction on murder, but had to concede that only a conviction on culpable homicide was justified, as the accused acted negligently under the circumstances. The notion that a battered (provoked) wife/husband/partner who kills her/his abusive husband/wife/partner may or can invoke private defence (self-defence) has rarely been considered by our courts. Provocation or emotional distress, in principle, influences the voluntary act committed by the accused and/or the criminal capacity of the accused and may affect the element of intention, but seldom has any bearing on the element of unlawfulness. After all, private defence requires an unlawful, immediate or imminent human attack perpetrated upon the accused or another person. Since the disappointing decision in S v Eadie (2002 1 SACR 633 (SCA)), in which the defence of non-pathological criminal incapacity due to provocation was effectively abolished (battered wives now have to rely on sane automatism, which is difficult to prove), battered wives who now kill their abusive husbands/partners are “left in the lurch” as it were, specifically in view of systematic assaults/attacks perpetrated upon them by their abusive partners. From a legal point of view it seems as though a “reconfiguration” of the principles of criminal law in these instances is called for. The “reconfiguration” of the defence essentially relates to the material requirements for the unlawful human attack, as well as the requirements for the lawful fending off the attack, specifically in context of domestic violence. It is for this reason that the judgment under discussion is particularly instructive and to be noted.